2020
DOI: 10.3390/plants9111624
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Low-Chill Blueberry Vaccinium corymbosum L. Tissue Culture Practices

Abstract: The demand for blueberry Vaccinium corymbosum L. (and hybrids) plants has significantly increased in the last 30 years due to its market expansion. In vitro propagation of sterile plants are required for commercial purposes but also for research applications such as plant transformation. Thus far, tissue culture characteristics of the tropical-adapted blueberry have been scarcely studied. In this study we present the following findings: (i) zeatin, a hormone used to promote plant growth, should be used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 52 publications
1
19
0
4
Order By: Relevance
“…The results of this study showed that when using 1.5% NaClO for 8 min, and then 0.1% HgCl 2 for 2 min for explant surface sterilization, the survival rate (viability) was higher than 85 % ('Biloxi': 86.67 %; 'Bluecrop': 93.33 %). However, our results agree with Cappai et al [29], pointing out that it depends on the genotype introduced in the in vitro culture conditions, in fact, modifications of the exposure (in time and concentration) to the disinfectant compound(s) can lead to significant variations in the results.…”
Section: Micropropagation Phasesupporting
confidence: 91%
“…The results of this study showed that when using 1.5% NaClO for 8 min, and then 0.1% HgCl 2 for 2 min for explant surface sterilization, the survival rate (viability) was higher than 85 % ('Biloxi': 86.67 %; 'Bluecrop': 93.33 %). However, our results agree with Cappai et al [29], pointing out that it depends on the genotype introduced in the in vitro culture conditions, in fact, modifications of the exposure (in time and concentration) to the disinfectant compound(s) can lead to significant variations in the results.…”
Section: Micropropagation Phasesupporting
confidence: 91%
“…However, to our knowledge, there is only one study of CRISPR-Cas9 targeted mutagenesis in blueberry (Omori et al, 2021 ). At the UF blueberry breeding program, we have advanced our understanding of the best tissue culture practices and most effective transformation markers (Cappai et al, 2020b ), laying the ground for CRISPR/Cas9 genome editing implementation in our breeding program. Using this technique, we can also take advantage of the knowledge accumulated from model crops to introduce novel allelic diversity in orthologs and accelerate the domestication process.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there is only one study of CRISPR-Cas9 targeted mutagenesis in blueberry (Omori et al , 2021). At the UF blueberry breeding program, we have advanced our understanding on the best tissue culture practices and most effective transformation markers (Cappai et al , 2020b), laying the ground for CRISPR/Cas9 genome editing implementation in our breeding program. Using this technique, we can also take advantage of the knowledge accumulated from model crops to introduce novel allelic diversity in orthologues and accelerate the domestication process.…”
Section: Resultsmentioning
confidence: 99%